THE BEHAVIORS ACCOMPANYING THE WRITING PROCESS IN SELECTED THIRD AND FOURTH GRADE NATIVE AMERICAN CHILDREN. - KASTEN, WENDY CHRISTINA. (The University of Arizona., 1984)
This study is designed to analyze in depth, the behaviors that accompany the writing process in six third and fourth grade Native American children. The children's writing, collected over a two year period, was observed by a team of researchers who carefully recorded revisions, rereading, subvocalization, resource use, stop-and-thinks, interruptions, and related talk while writing was taking place in the regular classroom setting. Four groups of questions were posed as a result of the observations focusing around the kinds of resources young writers use, the way they revised, the role of oral language during composing, and the relationship among the various observed behaviors. Young writers use both human resources and a wide variety of inanimate resources such as dictionaries, bulletin boards, and other classroom print to assist themselves and each other in spelling words, and making various other decisions about their writing. The subjects have differing strategies for revising their texts, but have spelling and neatness as their highest priorities. Children use more resources more extensively when they are encouraged to, when the materials are accessible, and collaboration among classmates is promoted. Approximately 90% of all oral language that takes place as children write is related directly to their writing. Oral language is a part of and seems to be important to all phases of writing, including strategies for consideration of what to write, collaboration with others and finding an audience. The use of oral language demonstrates that all aspects of the composing process including pre-writing, text generation, and revision or reconsideration of text are dynamically interacting as writers compose. There are important co-occurrence of types of behaviors including stop-and-thinks with interruptions, revisions with subvocalization, and revisions with resource use.